The Psychosomatic Assessment - Fava, G.A; Sonino, N. (Karger, 2012)
Patient reported outcomes have become more and more important in clinical practice and research. Evaluating subjective perceptions of patients has become mandatory for a full assessment of treatment responses. In this context, clinimetrics, the science of clinical measurements, provides unprecedented opportunities for psychosomatic assessment. This volume illustrates how this approach can be translated into everyday practice complementing and improving the medical interview. The most sensitive and reliable clinical methods are presented for evaluating specific psychosocial aspects of disease, i.e. childhood adversities, life events and chronic stress, lifestyle, sexual function, subclinical and affective disturbances, personality, illness behavior, well-being and family dynamics. Each chapter provides practical illustrations as to how crucial information can be obtained with specific methods individualized according to the patients' needs.